2021
DOI: 10.3390/biology10121283
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Coriander Plants on Human Emotions, Brain Electrophysiology, and Salivary Secretion

Abstract: Coriander is a popular herb with versatile applications. However, the current research about coriander medicinal values have been mainly focusing on its extracts while lacking in the relationship between living coriander plants and emotion. Therefore, this study aims to investigate the effects of coriander plants on human emotions and physiological activities. The results showed that the main Volatile organic compounds (VOCs) of coriander plants were 2-ethyl-1-hexanol, d-limonene, eucalyptol, benzyl alcohol, I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 49 publications
1
4
0
Order By: Relevance
“…Additionally, positive emotional tears production is related to a series of external secretions pathways, such as salivary secretion, gastric acid secretion and pancreatic secretion. It’s consistent with previous report that the activity of brain electrophysiological and salivary secretion can improve negative emotions of people and reduce amino acids (arginine, proline, histidine, and taurine) concentrations in saliva 26 . In summary, it is evident that secretion of either positive or negative emotional tears involves different biological activities.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Additionally, positive emotional tears production is related to a series of external secretions pathways, such as salivary secretion, gastric acid secretion and pancreatic secretion. It’s consistent with previous report that the activity of brain electrophysiological and salivary secretion can improve negative emotions of people and reduce amino acids (arginine, proline, histidine, and taurine) concentrations in saliva 26 . In summary, it is evident that secretion of either positive or negative emotional tears involves different biological activities.…”
Section: Discussionsupporting
confidence: 93%
“…Besides, positive emotional tears shedding is relevant to arginine and proline metabolism. Previous studies have identified the panel of metabolites associated with depression in animal models and patients 26, 27 . The levels of arginine, proline, taurine, glycine, and alanine are higher in depressed individuals than in healthy ones.…”
Section: Discussionmentioning
confidence: 99%
“…Positive emotional tears shedding is also associated with arginine and proline metabolism. The panel of metabolites associated with depression in animal models and patients has reported that levels of arginine, proline, taurine, glycine, and alanine are higher in depressed than in healthy individuals [ 26 , 27 ]. Microbial functions and metabolites, including proline, converging in glutamate/GABA metabolism are linked to depression.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there are data for α-pinene (T1) and linalool (T11) suggesting their effects on diseases, including stroke, ischemia, neuropathic pain, cognitive impairment (relevant to Alzheimer's disease and aging), anxiety, and depression [41]. Medicinal value in the treatment of anxiety syndromes has also been reported for dl-limonene (T3) and α-terpineol (T16) [94]. For thymol (T23), a potent anti-inflammatory agent, a specific cognitive enhancement activity has also been suggested in a rat model with dementia [95].…”
Section: Vocs Profile Of Honeymentioning
confidence: 99%